Diagnostic and treatment challenges of eating disorders after adolescent bariatric surgery: A case report. Issue 4 (11th May 2020) - Williams, Dominique; Chaves, Eileen; McKnight, Erin; Eneli, Ihuoma
Abstract: It is increasingly evident that bariatric surgery is an effective treatment option to manage severe obesity and its comorbidities in adolescent patients. This case report follows an adolescent who developed a restrictive eating disorder within months after bariatric surgery. Identifying and treating eating disorders after bariatric surgery can be difficult due to the conflicting goals of weight loss after surgery and weight gain in treatment of a restrictive eating disorder. Moreover, treating older adolescents can be challenging when they refuse treatment or go against medical advice. As more adolescents choose bariatric surgery, it is imperative that clinicians remain sensitive to weight‐related outcomes, possible eating disorders and adolescent autonomy. Early collaboration between weight management and eating disorder programs is essential.